Trace Element Contents of Edible Macrofungi Growing in Adiyaman, Turkey - Kaya, A.; Bag, H. (Asian Journal of Chemistry, 2010)
Trace elements (Al, B, Cd, Co, Cr, Cu, Fe, Mn, Ni, Pb, Sn and Zn) content were determined by inductively coupled plasma optical emission spectroscopy (ICP-OES) in the samples of edible mushroom fruiting bodies of 24 species (Agaricus campestris, Agrocybe aegerita, Agrocybe dura, Armillaria mellea, Boletus queletii, Coprinellus disseminatus, Coprinellus micaceus, Coprinus comatus, Gymnopus dryophilus, Lentinus tigrinus, Leucoagaricus leucothites, Lycoperdon molle, Macrocystidia cucumis, Macrolepiota excoriate, Macrolepiota mastoidea, Pleurotus ostreatus, Pluteus romellii, Psathyrella candolleana, Rhizopogon luteolus, Russula subterfurcata, Stropharia coronilla, Suillus luteus, Volvariella gloiocephala and Volvariella hypopithys) collected from Adiyaman, Turkey. Trace element amouts in mushrooms varied widely depending on the site and mushroom species investigated.